Formation conditions of deep to ultra-deep large composite buried-hill hydrocarbon reservoirs in offshore Bohai Bay Basin, China - Changgui XU; Haifeng YANG; Feilong WANG; Jingsong PENG (Petroleum Exploration and Development)
Based on the data from 3D seismic surveys, drilling, sidewall coring, thin sections, and tests, this paper analyzes Meso-Cenozoic geotectonic dynamics, buried-hill reservoir characteristics, and differential enrichment patterns of oil and gas in the buried hills, as well as case studies of typical reservoirs, to systematically discuss the conditions required for the formation of buried-hills and reservoirs and accumulations in the large oil and gas fields in deep to ultra-deep composite buried hills in the Bohai Sea.. The key findings are as follows. First, deep to ultra-deep composite buried hills developed in the offshore Bohai Bay Basin primarily due to the double-episode destruction of the North China Craton in the Yanshanian and Himalayan.. The Tanlu Fault’s activity and the destruction of the North China Craton worked together to create the destruction center, which moved and converged episodically from the Bohai Bay Basin’s margins towards the Bozhong Depression. This led to the formation of two development zones for composite buried hills and an orderly process of mountain-building within the offshore Bohai Bay Basin. e. the middle and inner rim zones within the Bozhong Depression. Second, under the coupling of favorable lithologies and multi-stage structures, the middle and inner rim zones are favorable for the formation of reservoirs in fluid dissolution–pore/fracture zones underlying the weathering crust. Third, Massive hydrocarbons were produced along the middle and inner rim zones during the Episode II craton destruction, which caused overpressure. These hydrocarbons then moved to and accumulated in the composite buried hills. Excellent conditions for the accumulation of hydrocarbons are still present in the interior and lower portions of these buried hills. . These results encourage a change in buried hill research to investigate composite buried hills in three dimensions. It should be noted that the multi-stage volcanic structures in the inner rim zone of the depression and the deep to ultra-deep composite buried hill interiors in the middle rim zone are significant successor areas for further Bohai Sea exploration.